Mitochondrial DNA lineages determine tumor progression through T cell reactive oxygen signaling - Tal Yardeni; Arnold Z. Olali; Hsiao-Wen Chen; Liqing Wang; Jeffrey A. Haltom; Angi Zenab; Ryan Morrow; Arrienne Butic; Deborah G. Murdock; Katrina G. Waymire; Grant R. MacGregor; Ben Boursi; et al. (Proceedings of the National Academy of Sciences, 2025)
Mitochondrial DNA (mtDNA) is highly polymorphic, and host mtDNA variation has been associated with altered cancer severity. To determine the basis of this mtDNA–cancer association, we analyzed conplastic mice with the C57BL/6J (B6) nucleus but two naturally occurring mtDNA lineages, mtDNA B6 and mtDNA NZB , where mtDNA NZB mitochondria generate more oxidative phosphorylation (OXPHOS)-derived reactive oxygen species (mROS). In a cardiac transplant model, mtDNA B6 Foxp3+ T regulatory (Treg) cells supported long-term allograft survival, whereas mtDNA NZB Treg cells failed to suppress host T effector (Teff) cells, leading to acute rejection. When challenged with melanoma or colon cancer cells, the mtDNA NZB mice exhibited strikingly impaired tumor growth while mtDNA B6 mice showed Treg-dependent inhibition of Teff cells and allowed rapid tumor growth. Transcriptional analysis showed that activation of mtDNA NZB Teff cells increased mitochondrial gene expression while activation of mtDNA NZB Treg cells impaired mitochondrial gene expression and resulted in mtDNA NZB Treg cell exhaustion. Induction of the mitochondrially targeted catalytic antioxidant, mCAT, in hematopoietic cells normalized mtDNA NZB Treg function in both transplant and tumor models, indicating a key role for mROS in promoting Treg dysfunction. Anti-PD-L1 therapy did not modulate these effects, indicating that modulation of host mitochondrial function provides an independent approach for enhancing tumor cell destruction.